Pembaharuan Hukum Perlindungan Jurnalistik Dalam Rangka Kebebasan Pers Berdasarkan Nilai Keadilan - Sara, Rineke; Lineker, Tyson; Daton, Febianus Seran; Batubara, Muhamad Iqbal Zein (Pascasarjana UDA, 2023)
Freedom of the press as a pillar of democracy often faces threats from regulations that are open to multiple interpretations, such as articles in the Electronic Information and Transactions Law (UU ITE) that can be used to criminalize journalists and limit the public's right to information. This study aims to reconstruct ideal regulations based on the value of justice by placing press freedom as the main priority, as well as guaranteeing the public's right to obtain correct and transparent information. The study uses a normative legal method with a legislative and conceptual approach to evaluate the weaknesses of existing regulations, especially the ITE Law and the Press Law, and to provide concrete recommendations. The results of the study underline the importance of revising the multi-interpretable articles in the ITE Law, strengthening the Press Law as a legal umbrella for press freedom, and developing a more efficient dispute resolution mechanism to protect journalists from legal or physical intimidation. The main conclusion shows that collaboration between the government, supervisory institutions, and the community is needed to ensure a safe environment for journalists, so that press freedom can be realized optimally as the main link between the public and information.